2014
DOI: 10.3389/fonc.2014.00312
|View full text |Cite
|
Sign up to set email alerts
|

SBRT for the Primary Treatment of Localized Prostate Cancer: The Effect of Gleason Score, Dose and Heterogeneity of Intermediate Risk on Outcome Utilizing 2.2014 NCCN Risk Stratification Guidelines

Abstract: Purpose: To report an update of our previous experience using stereotactic body radiation therapy (SBRT) for the primary treatment of prostate cancer, risk stratified by the updated National Comprehensive Cancer Network (NCCN) version 2.2014, reporting efficacy and toxicity in a community hospital setting.Methods: From 2007 to 2012, 142 localized prostate cancer patients were treated with SBRT using CyberKnife. NCCN guidelines Version 2.2014 risk groups analyzed included very low (20%), low (23%), intermediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 22 publications
(28 reference statements)
4
24
0
1
Order By: Relevance
“…In our current study, acute and late GU and GI toxicity were low. Minimal GU and GI toxicities have also been reported in other studies using SBRT doses of 35 - 36.25 Gy delivered in 5 fractions [ 19 , 24 , 30 - 34 ]. King, et al reported urinary Grade 1, 2, and 3 toxicity in 23%, 5%, and 3% of patients, respectively, and Grade 1 and 2 rectal toxicity in 12.5% and 2% of patients, respectively [ 33 ].…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…In our current study, acute and late GU and GI toxicity were low. Minimal GU and GI toxicities have also been reported in other studies using SBRT doses of 35 - 36.25 Gy delivered in 5 fractions [ 19 , 24 , 30 - 34 ]. King, et al reported urinary Grade 1, 2, and 3 toxicity in 23%, 5%, and 3% of patients, respectively, and Grade 1 and 2 rectal toxicity in 12.5% and 2% of patients, respectively [ 33 ].…”
Section: Discussionsupporting
confidence: 59%
“…The late Grade 3 or greater rectal toxicity correlated with the rectal wall receiving 50 Gy > 3 cm. Bernetich, et al showed improved freedom from biochemical failure in intermediate and high-risk patients treated with 37.5 Gy compared to 35-36.25 Gy; however, patients receiving 37.5 Gy experienced slightly higher Grade 3 GU toxicity [ 34 ]. In our study, we were not able to stratify by dose because the majority of patients were treated with 36.25 Gy in 5 fractions, and there were limited numbers of patients treated with higher doses, thus, limiting our ability to conduct analysis with adequate statistical power to assess correlations between dose and incidence of toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, as in metaanalyses and in the aforementioned large single center patients’ group, the authors also report very good results in the smaller single center series. Bernetich et al, in a group of 142 patients irradiated to a TD of 35-36.25 Gy in 5 fractions, present a 5-year 100% success rate bFFS for very low risk (VLR), 91.7% for LR, 90% for IR and 86.7% for HR patients [ 20 ]. Fuller et al report a decrease in PSA median from 5.4 before treatment (4 x 9.5 Gy) to 0.05 ng/ml 5 years later (bFFS 96.2%) in the group of 79 LR and IR patients [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous publication described the effect of higher SBRT dose on outcome and will not be further discussed here (9). …”
Section: Resultsmentioning
confidence: 99%